2016
DOI: 10.21276/ambi.2016.03.1.ga01
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological Innovations inAquaculture

Abstract: Aquaculture is gaining commendable importance to meet the required protein source for ever increasing human population. The aquaculture industry is currently facing problems on developing economically viable production systems by reducing the impact on environment. Sustainable and enhanced f ish production from aquaculture may be better achieved through application of recent biotechnological innovations. Utilisation of transgenic technology has led to production of f ishes with faster growth rate with disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Moreover, gastropods also act as predators and filter feeders that provide organic materials in the marine ecosystem (Sharma et al 2013;Bhosale et al 2016). A previous study of the diversity of gastropods revealed a high abundance of gastropods such as Pomacea canaliculata (Golden Apple Snail) in rivers and lakes in Bukidnon, Philippines (Galan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, gastropods also act as predators and filter feeders that provide organic materials in the marine ecosystem (Sharma et al 2013;Bhosale et al 2016). A previous study of the diversity of gastropods revealed a high abundance of gastropods such as Pomacea canaliculata (Golden Apple Snail) in rivers and lakes in Bukidnon, Philippines (Galan et al 2015).…”
Section: Introductionmentioning
confidence: 99%